Establishing a National Community of Practice for Newborn Screening Follow-Up - Erin Darby; John Thompson; Carol Johnson; Sikha Singh; Jelili Ojodu (MDPI AG, 2021)
Newborn screening (NBS) follow-up programs in the United States are managed at the state level, leaving limited opportunities for collaboration across programs and coordinated resource sharing. The Newborn Screening Technical assistance and Evaluation Program (NewSTEPs), a program of the Association of Public Health Laboratories (APHL), has established a national community of practice for NBS follow-up by creating a network of follow-up staff and stakeholders through education and engagement opportunities. The activities of NewSTEPs in support of NBS follow-up have strengthened information dissemination, collaboration, data collection and technical assistance-driven mentorship across the national system.